2020
DOI: 10.14814/phy2.14506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interval walking training managed through smart mobile devices on albuminuria and leptin/adiponectin ratio in patients with type 2 diabetes

Abstract: Background Interval walking training has demonstrated more pronounced positive effects on physical fitness and metabolism in type 2 diabetes (T2D), compared to continuous walking. One of the pathogenic mechanisms of T2D is associated with derangements in leptin/adiponectin axis, which might predispose affected individuals to vascular inflammation and albuminuria. The aim of this study was to investigate the effects of interval walking training delivered through smart mobile devices upon albuminuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Of those 46 studies, 25 met the inclusion criteria, and the other 21 studies were excluded: (A) 15 did not include control groups, (B) two included ages less than 18 years, (C) one used acute training; (D) three did not report complete data (lacked either pre-test or post-test data). In total, 25 RCTs (Ahmadi et al, 2012; Annibalini et al, 2017; Baigzadeh et al, 2020; Balducci et al, 2010; Boudou et al, 2003; Brooks et al, 2007; Corpeleijn et al, 2007; Doğan Dede et al, 2014; Gokulakrishnan et al, 2017; Ibáñez et al, 2010; Jorge et al, 2011; Kadoglou, Iliadis, Angelopoulou, et al, 2007; Kadoglou, Iliadis, Liapis, et al, 2007; Ku et al, 2010; Mendham et al, 2014; Moghadasi et al, 2011; Moghadasi et al, 2012; Okada et al, 2010; Parsian et al, 2012; Rokling-Andersen et al, 2007; Sixt et al, 2010; Sokolovska et al, 2020; Wu et al, 2011; Yang et al, 2020; Zhang et al, 2017) were included ( N = 1257 participants; 679 in the intervention groups, and 578 in the control groups). A flow diagram of the study search and selection, including reasons for exclusion, is shown in Figure 1.
Figure 1.PRISMA flow diagram of the literature search.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of those 46 studies, 25 met the inclusion criteria, and the other 21 studies were excluded: (A) 15 did not include control groups, (B) two included ages less than 18 years, (C) one used acute training; (D) three did not report complete data (lacked either pre-test or post-test data). In total, 25 RCTs (Ahmadi et al, 2012; Annibalini et al, 2017; Baigzadeh et al, 2020; Balducci et al, 2010; Boudou et al, 2003; Brooks et al, 2007; Corpeleijn et al, 2007; Doğan Dede et al, 2014; Gokulakrishnan et al, 2017; Ibáñez et al, 2010; Jorge et al, 2011; Kadoglou, Iliadis, Angelopoulou, et al, 2007; Kadoglou, Iliadis, Liapis, et al, 2007; Ku et al, 2010; Mendham et al, 2014; Moghadasi et al, 2011; Moghadasi et al, 2012; Okada et al, 2010; Parsian et al, 2012; Rokling-Andersen et al, 2007; Sixt et al, 2010; Sokolovska et al, 2020; Wu et al, 2011; Yang et al, 2020; Zhang et al, 2017) were included ( N = 1257 participants; 679 in the intervention groups, and 578 in the control groups). A flow diagram of the study search and selection, including reasons for exclusion, is shown in Figure 1.
Figure 1.PRISMA flow diagram of the literature search.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies were carried out in Iran (5), USA (1), Japan (1), South Korea (1), Greece (2), Finland (1), Germany (1), China (2), Turkey (1), India (1), Latvia (1), Taiwan (1), France (1), Spain (1), Italy (2), Brazil (1), Australia (1), and Norway (1). Based on biological sex classification criteria, nine studies exclusively recruited male participants (Ahmadi et al, 2012; Annibalini et al, 2017; Baigzadeh et al, 2020; Boudou et al, 2003; Gokulakrishnan et al, 2017; Mendham et al, 2014; Moghadasi et al, 2011, 2012; Parsian et al, 2012), two studies exclusively recruited female participants (Ibáñez et al, 2010; Ku et al, 2010), and 14 studies recruited both males and females (Balducci et al, 2010; Brooks et al, 2007; Corpeleijn et al, 2007; Doğan Dede et al, 2014; Jorge et al, 2011; Kadoglou, Iliadis, Angelopoulou, et al, 2007; Kadoglou, Iliadis, Liapis, et al, 2007; Okada et al, 2010; Rokling-Andersen et al, 2007; Sixt et al, 2010; Sokolovska et al, 2020; Wu et al, 2011; Yang et al, 2020; Zhang et al, 2017). Based on age classification criteria, in 24 studies the mean age of participants varied from 40 to 67 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations